Gender Culture Among Students - Saydullayeva, A. R.; Abdumalikova, M. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article characterizes gender equality as a value of law in the discourse of anthropological trends. The main components of gender equality are characterized. The right to differences in the aspect of gender approach in law is considered.